Mobile applications for autism - Kyriakaki, Evdoxia; Karabatzaki, Zoe; Salapata, Yolanda (Eximia, 2023)
The rapid development of technology in recent years has increased the interest of educators, researchers, families and therapists of children with autism in the possibilities that digital technologies offer regarding the treatment, education, support and remedy for the plethora of difficulties they face. This particular interest is further enhanced by the need to provide these children with effective interventions through the use of applications that will engage and significantly assist them. For this reason, empirical studies concerning assistive technology products have been constantly increasing; such products promise that they can make up for all the deficits and meet the needs that people in the autism spectrum have in diverse areas, such as communication, social integration and skill acquisition. According to all the above, this research aims to present the mobile applications used in autism. Thus, in the first chapter, there will be a definition of autism and a presentation of its key features. Furthermore, in the second chapter, assistive technology in the context of autistic disorders will be discussed as well as the possible advantages of portable applications. Finally, in the third chapter, there will be various examples of such applications.